Identification of host tRNAs preferentially recognized by the Plasmodium surface protein tRip. Issue 18 (16th September 2021) - Cela, Marta; Théobald-Dietrich, Anne; Rudinger-Thirion, Joëlle; Wolff, Philippe; Geslain, Renaud; Frugier, Magali
Abstract: Malaria is a life-threatening and devastating parasitic disease. Our previous work showed that parasite development requires the import of exogenous transfer RNAs (tRNAs), which represents a novel and unique form of host–pathogen interaction, as well as a potentially druggable target. This import is mediated by tRip (tRNA import protein), a membrane protein located on the parasite surface. tRip displays an extracellular domain homologous to the well-characterized OB-fold tRNA-binding domain, a structural motif known to indiscriminately interact with tRNAs. We used MIST (Microarray Identification of Shifted tRNAs), a previously established in vitro approach, to systematically assess the specificity of complexes between native Homo sapiens tRNAs and recombinant Plasmodium falciparum tRip. We demonstrate that tRip unexpectedly binds to host tRNAs with a wide range of affinities, suggesting that only a small subset of human tRNAs is preferentially imported into the parasite. In particular, we show with in vitro transcribed constructs that tRip does not bind specific tRNAs solely based on their primary sequence, hinting that post-transcriptional modifications modulate the formation of our host/parasite molecular complex. Finally, we discuss the potential utilization of the most efficient tRip ligands for the translation of the parasite's genetic information.